Hollow-Core Magnetic Colloidal Nanocrystal Clusters with Ligand-Exchanged Surface Modification as Delivery Vehicles for Targeted and Stimuli-Responsive Drug Release - Li, D.; Tang, J.; Guo, J.; Wang, S.; Chaudhary, Deeptangshu; Wang, C. (Wiley - V C H Verlag GmbH & Co. KGaA, 2012)
The fabrication of hierarchical magnetic nanomaterials with welldefined structure, high magnetic response, excellent colloidal stability, and biocompatibility is highly sought after for drug-delivery systems. Herein, a new kind of hollow-core magnetic colloidal nanocrystal cluster (HMCNC) with porous shell and tunable hollow chamber is synthesized by a one-pot solvothermal process. Its novelty lies in the “tunability” of the hollow chamber and of the pore structure within the shell through controlled feeding of sodium citrate and water, respectively. Furthermore, by using the ligand-exchange method, folate-modified poly(acrylic acid) was immobilized on the surface of HMCNCs to create folatetargetedHMCNCs (folate-HMCNCs), which endowed them with excellent colloidal stability, pH sensitivity, and,more importantly, folate receptor-targeting ability. These assemblages exhibited excellent colloidal stability in plasma solution. Doxorubicin (DOX), as a model anticancer agent, was loaded within the hollow core of these folate-HMCNCs (folate-HMCNCs-DOX), and drug-release experiments proved that the folate-HMCNCs-DOX demonstrated pH-dependent release behavior. The folate-HMCNCs-DOXassemblages also exhibited higher potent cytotoxicity to HeLa cells than free doxorubicin. Moreover, folate-HMCNCs-DOX showed rapid cell uptake apart from the enhanced cytotoxicity to HeLa cells. Experimental results confirmed that the synthesized folate-HMCNCs are smart nanovehicles as a result of their improved folate receptor-targeting abilities and also because of their combined pH- and magnetic-stimuli response for applications in drug delivery.